2011
DOI: 10.1007/s00380-011-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of the ascending aorta and serum alpha 1-antitrypsin level in patients with bicuspid aortic valve

Abstract: Predictors of aortic dilatation are not well described in patients with bicuspid aortic valves (BAV). This study sought to examine the relationship between proximal aortic dilatation and matrix metalloproteinase-9 (MMP-9) and alpha 1-antitrypsin (α1AT) levels in patients with BAV. All patients underwent echocardiography using a standard protocol, and aortic measurements were taken in end-diastole. We studied 82 patients with BAV and categorized them into two groups according to aortic dimensions corrected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…On the contrary, Ikonomidis et al [28] advocated the predictive value of plasma MMP-9 for identifying ascending aortic aneurysm among BAV patients, regardless of their aortic valve status. We hypothesized that there might be different aortic vessel wall shear stress thresholds for the activation of these two enzymatic proteins, since MMP-2 was synthesized by resident cells within aortic wall such as fibroblasts and smooth muscle cells and expressed ubiquitously under physiological conditions, while MMP-9 existed mainly not only in neutrophils but also in other cell types responding to specific stimuli [29][30][31][32]. The up-regulated MMP-9 could induce endothelial dysfunction and further accelerate ascending aortic dilatation in BAV patients with severe stenosis via activation of endothelial MMP-2 [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Ikonomidis et al [28] advocated the predictive value of plasma MMP-9 for identifying ascending aortic aneurysm among BAV patients, regardless of their aortic valve status. We hypothesized that there might be different aortic vessel wall shear stress thresholds for the activation of these two enzymatic proteins, since MMP-2 was synthesized by resident cells within aortic wall such as fibroblasts and smooth muscle cells and expressed ubiquitously under physiological conditions, while MMP-9 existed mainly not only in neutrophils but also in other cell types responding to specific stimuli [29][30][31][32]. The up-regulated MMP-9 could induce endothelial dysfunction and further accelerate ascending aortic dilatation in BAV patients with severe stenosis via activation of endothelial MMP-2 [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study showed that in patients presenting with bicuspid AV, plasma concentrations of α 1AT were higher in those patients with ascending aortic dilatation compared to the nondilated group [9]. Patients with bicuspid AV and a rapid progression of aortic dilatation have a more extensive cardiovascular risk profile including higher blood glucose levels, a higher incidence of coronary artery disease, more tobacco use, and a higher National Heart, Lung and Blood Institute 10-year risk of developing coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…MMP isoform 9 expression in aneurysmal BAV aortic tissue has been shown [14,40]. Yet several other investigations did not find meaningful differences in the plasma expression, mRNA, or allelic makeup of MMP in affected individuals [41][42][43][44].…”
Section: Mechanism Of Bav-related Aortic Dilatationmentioning
confidence: 95%